A STUDY ON PATTERN DAMAGE OF FINGER JOINTS IN BAMBOO LAMINATED BEAMS - Rivani, Agus (MEKTEK, 2006)
The aim of this study was to know the pattern damage of finger joints in bamboo laminated beams. The dimension of laminated beams were manufactured in 1200 mm length, 140 mm deep and 50 mm wide, which consisted of horizontally laminate of 5 mm in thickness. The finger joint consisted of two variations that were horizontal and vertical directions. One variation of other beam was manufactured in the form of clear straight beams as comparator parameters. The bending shear test was conducted with a three-point static bending.The result of research indicated that the joint areas, which the parameter of glue spread have to influence on the strength. Consequently, degradation of strength occurs on all of adhesive jointed beam can reach 48%, while the optimum strength of jointed beams can reach 82% of clear straight beams. This research identify that the pattern damage of laminated beams tends on a mixed mode failure between tension and compression. The strength of vertically finger joint more effective than horizontally finger joint